The potential for microfluidics in electrochemical energy systems. Issue 11 (23rd September 2016) - Modestino, M. A.; Fernandez Rivas, D.; Hashemi, S. M. H.; Gardeniers, J. G. E.; Psaltis, D.
Abstract : Energy storage technologies based on microfluidic electrochemical devices show optimal conversion efficiencies, and have potential to reach large-scale applications. Abstract : Flow based electrochemical energy conversion devices have the potential to become a prominent energy storage technology in a world driven by renewable energy sources. The optimal design of these devices depends strongly on the tradeoffs between the losses associated with multiple transport processes: convection and diffusion of reactants and products, migration of ionic species, and electrical charge transport. In this article we provide a balanced assessment of the compromise between these losses and demonstrate that for a broad range of electrochemical reactors, the use of microfluidics can enhance the energy conversion efficiency. Moreover, we propose proven scale-up strategies of microelectrochemical reactors which could pave the way to the large scale implementation of energy microfluidic systems.